Tilling the truth - Henry, Julia, 1962- (Henry, Julia, 1962- Garden Squad mystery, 2019)
"It's August in Goosebush, Massachusetts, and go-getter retiree Lilly Jayne and her youthful senior pals show no sign of slowing down during the lazy days of summer. But when murder mows over a pesky local, could a Garden Squad member be nurturing a deadly second act?"--Publisher description